Organometallic synthesis of nanomaterials for catalytic carbon dioxide conversion - Häfele, L (2022)
This thesis investigates a series of organometallic reactions to produce colloidal nanoparticles (Cu and Cu2O) and layered metal hydroxides (Zn or Cu). The general synthesis involves reacting an organometallic precursor, with a ligand (e.g. a carboxylic acid) and either exposure to hydrogen gas, water or air. The synthesis occurs in organic solvents at temperatures from room temperature to 110 °C. These reactions produce nanomaterials which are soluble in various organic solvents. Chapter 1: The first chapter introduces the research topics of this thesis by outlining the relevant literature. The characteristics and properties of nanomaterials are described, alongside their roles in various catalyses, with a focus on carbon dioxide utilisation. Chapter 2: This chapter describes the synthesis and characterisation of colloidal Cu and Cu2O nanoparticles, capped with oxygen-containing anionic, bidentate carboxylate ligands (i.e. nonanoate, 2-[2-(2-methoxyethoxy)ethoxy]acetate) or a sulphur-containing anionic, bidentate dithicarboxylate ligand (i.e. dithiononanoate). The effects of ligand substituents on the solubility and stability of the resulting nanoparticles in common organic solvents (toluene, THF, acetone and methanol), as well as their ease of removal from the particle surface by thermal ligand degradation was evaluated. Ligand exchange reactivity of the carboxylate and dithiocarboxylate ligands is probed to evaluate the relationship between colloidal nanoparticle stability and ligand binding-group identity. This research provides understanding of the conditions required for colloidal nanoparticle synthesis and a means to make colloidal inks for solution-phase thin film deposition. Chapter 3: This chapter will describe efforts to synthesise a hydrotalcite-like catalyst precursor for the conversion of CO2 to methanol. Efforts to isolate copper-containing Layered Metal Hydroxides (LMH) via the controlled hydrolysis of organometallic precursors is discussed. The synthesis routes tested thus far have been unsuccessful leading to separated phases over the copper-based material. Chapter 4: This chapter describes the use of colloidal Layered Zinc Hydroxides (LZH) as a novel catalytic stystem for the ring opening copolymerisation (ROCOP) of propylene oxide (PO) and CO2 to provide polypropylene carbonate (PPC). The synthesis and characterisation of the catalysts is outlined. Then the catalytic performance, under varying temperatures, pressures and catalyst loading, is discussed. Chapter 5: This chapter summarises the results and outlines various future directions for this research. Chapter 6: The final chapter details the experimental protocols and methods used to produce and characterise the products.